ARP Case Report Nº 18: Malignant Peritoneal Mesothelioma - Correia,David Campos (2020)
Abstract 72 year-old male referred to our hospital due to a 5-month history of dry cough, increasing abdominal discomfort and feeling of abdominal fullness. Abdominal ultrasound and contrast- enhanced CT were performed.